Comparison of simplified and comprehensive methods for assessing the index of microvascular resistance in heart transplant recipients. Issue 2 (3rd November 2015) - Geir Solberg, Ole; Aaberge, Lars; Ragnarsson, Asgrimur; Aas, Marit; Endresen, Knut; Šaltytė Benth, Jūratė; Gullestad, Lars; Stavem, Knut
Abstract : Objectives: The objectives of the present study were to compare a simplified and a comprehensive method of estimating the index of microvascular resistance (IMR) and assess the changes from 7–11 weeks to 1 year after heart transplant (HTx). Background: he IMR is specific to the microvasculature and reflects the status of the microcirculation in cardiac patients and can be estimated via a simplified method (IMRs ) or a comprehensive method (IMRc ). The calculation for the latter includes coronary wedge pressure and central venous pressure. Methods: Consecutively transplanted patients ( n  = 48) underwent left and right heart catheterization including physiological evaluation at two time points post‐HTx. The agreement between the values of IMR obtained using the IMRs and IMRc methods were assessed using Bland–Altman analysis. The agreements and differences were assessed using mixed model analysis. Results: The mean bias between IMRs and IMRc was 1.3 mm Hg·s (95% limits of agreement: −1.2, 3.8 mm Hg). Between 7–11 weeks and 1 year post‐HTx there was a significant decline in IMRs values ( P  = 0.03) but a smaller and statistically nonsignificant decline in IMRc values ( P  = 0.13). The significant difference ( P  = 0.04) between IMRc and IMRs 7–11 weeks post‐HTx was no longer present at 1 year ( P  = 0.24). Conclusions: The IMRs method resulted in slightly higher IMR estimates and exhibited a somewhat larger change over the 10‐month follow‐up period than the IMRc method. However, the differences between the methods were small and unlikely to be of clinical importance. © 2015 Wiley Periodicals, Inc.